Comparative Analysis of Stock Prices, Stock Returns, Abnormal Returns and Trading Volume Before and After the Announcement of Covid-19 - Suryanti, Anggi Aprilia; Ahyaruddin, Muhammad; Fitriana, Nur (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study analyzes significant differences in stock prices, stock returns, abnormal returns, and stock trading volume of telecommunications companies before and after the announcement of COVID-19 in Indonesia. The analysis was conducted using Paired Sample T-Test for normally distributed data and Wilcoxon Signed Rank Test for non-normal data, with the help of Microsoft Excel 2010 and SPSS-24 in data processing. The results showed that the COVID-19 announcement had a significant effect on the four variables. Stock prices decreased due to selling pressure triggered by economic uncertainty, so investors became more selective. Although stock prices decreased, trading volume increased due to panic selling. Investors try to minimize risk by releasing stocks and shifting their investments to safer instruments. This finding reinforces the Efficient Market Theory, which states that information related to the COVID-19 pandemic is quickly reflected in stock prices and trading volumes. From a policy perspective, these results emphasize the importance of risk mitigation strategies for investors as well as the government's role in stabilizing the market to reduce the impact of volatility due to global events. The uniqueness of this study lies in analyzing the impact of COVID-19 on the telecommunications sector in Indonesia, which has rarely been studied.